2012
DOI: 10.1128/aac.00468-11
|View full text |Cite
|
Sign up to set email alerts
|

Ultrashort Peptide Bioconjugates Are Exclusively Antifungal Agents and Synergize with Cyclodextrin and Amphotericin B

Abstract: Many natural broad-spectrum cationic antimicrobial peptides (AMPs) possess a general mode of action that is dependent on lipophilicity and charge. Modulating the lipophilicity of AMPs by the addition of a fatty acid has been an effective strategy to increase the lytic activity and can further broaden the spectrum of AMPs. However, lipophilic modifications that narrow the spectrum of activity and exclusively direct peptides to fungi are less common. Here, we show that short peptide sequences can be targeted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
34
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 41 publications
(44 reference statements)
3
34
0
Order By: Relevance
“…Among these 30 S. epidermidis were found to carry mec gene. Various reports on methicillin carriage in S. epidermidis showed it to have a distribution rate of 69–84% (Lebeaux et al 2011) and is in accordance with the results of current study. In addition, all of the S. hominis , S. saprophyticus , S. cohnii and S. sciuri isolates were also found to have the presence of mec gene.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Among these 30 S. epidermidis were found to carry mec gene. Various reports on methicillin carriage in S. epidermidis showed it to have a distribution rate of 69–84% (Lebeaux et al 2011) and is in accordance with the results of current study. In addition, all of the S. hominis , S. saprophyticus , S. cohnii and S. sciuri isolates were also found to have the presence of mec gene.…”
Section: Discussionsupporting
confidence: 93%
“…Based on the classes of the mec gene complex and the ccr gene type there are 11 different SCC mec types for S. aureus which itself highlights its importance. But SCC mec elements are likely to be more diverse in MRCoNS due to continuous generation of new composite cassettes that do not fit within the classification proposed for MRSA (Lo et al 2010; Lebeaux et al 2011; Zong et al 2011). Another genetic element, the insertion sequence IS256 which is mainly involved in phase variation of biofilm forming CoNS has been identified to have coexistence with mec gene (Kozitskaya et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The action mode of AMPs has been investigated in many studies. Many AMPs were found that they could bind with the membrane of microbes and then disrupt the integrity of cell membrane (Arnusch et al 2012). There are mainly three models, the barrel-stave model, the toroidal pores model, and the carpet model (Chih et al 2015), which are widely accepted to describe the membrane-active action mode.…”
Section: Discussionmentioning
confidence: 99%
“…A number of these naturally occurring molecules are endowed with antimicrobial activities; however, their use is restricted to topical applications owing to their cytotoxicity (19). Extensive research in this field has led to the development of synthetically designed AMPs and peptidomimetics having in vitro antimicrobial activity and reduced cytotoxicity making them suitable candidates for antimicrobial drug design (20)(21)(22). Synthetically designed peptides have opened up immense opportunities in the field of drug design allowing modification to obtain optimal potency and selectivity.…”
Section: Introductionmentioning
confidence: 99%